2005
DOI: 10.1159/000081988
|View full text |Cite
|
Sign up to set email alerts
|

The Pathogenesis of Gastrointestinal Bacterial Overgrowth

Abstract: The normal indigenous intestinal microflora consists of about 1015 bacteria that under physiological conditions reside mainly in the lower gastrointestinal tract. Bacterial overgrowth implies abnormal bacterial colonization of the upper gut, resulting from failure of specific defense mechanisms restricting colonization under physiological conditions. At present two types of bacterial overgrowth with defined pathogenesis can be distinguished: (1) gastric overgrowth with upper respiratory tract microf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
91
0
12

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(105 citation statements)
references
References 267 publications
(289 reference statements)
1
91
0
12
Order By: Relevance
“…Gastric acidity, anatomical integrity of the digestive tract, peristaltic activity of the bowel, immunglobulin A plays a major role in maintaining the balance between the intestinal microflora and host mechanisms fails bacterial over studies, small intestinal bacterial over growth (SIBO) is defined as the microbiological presence of more than10 colony forming units (CFU) per ml of Various studies showed the relationship between the derangement of gut flora and increased prevalence of SIBO in cirrhotic patients. 5,6 Decrease in small bowel motility and increasein adrenergic activity in cirrhotic patients may lead bacterial overgrowth. [5][6][7] In addition to the range of symptoms and consequences of SIBO per se, increasing evidence suggests tha of intestinal flora is of substantial clinical relevance to Institute of Medical Gastroenterology, Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric acidity, anatomical integrity of the digestive tract, peristaltic activity of the bowel, immunglobulin A plays a major role in maintaining the balance between the intestinal microflora and host mechanisms fails bacterial over studies, small intestinal bacterial over growth (SIBO) is defined as the microbiological presence of more than10 colony forming units (CFU) per ml of Various studies showed the relationship between the derangement of gut flora and increased prevalence of SIBO in cirrhotic patients. 5,6 Decrease in small bowel motility and increasein adrenergic activity in cirrhotic patients may lead bacterial overgrowth. [5][6][7] In addition to the range of symptoms and consequences of SIBO per se, increasing evidence suggests tha of intestinal flora is of substantial clinical relevance to Institute of Medical Gastroenterology, Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai,…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Decrease in small bowel motility and increasein adrenergic activity in cirrhotic patients may lead bacterial overgrowth. [5][6][7] In addition to the range of symptoms and consequences of SIBO per se, increasing evidence suggests tha of intestinal flora is of substantial clinical relevance to Institute of Medical Gastroenterology, Madras Medical College and Rajiv Gandhi Government General Hospital, Chennai,…”
Section: Introductionmentioning
confidence: 99%
“…Due to the bactericidal properties of the gastric and also bile acids, the stomach and proximal small intestine contain only few microorganisms. Patients with reduced gastric acid levels (achlorhydria or hypochlorhydria for example) may suffer from bacterial overgrowth and subsequent inflammatory or malignant complications (Friis-Hansen, 2006;Husebye, 2005;Naylor & Axon, 2003). With increasing distance from the stomach and…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a disease that incorporates various metabolic disturbances such as impaired glucose haemostasis, blood dyscrasias and hyperlipidemia. Major disturbances also include slower gut movement (gastroparesis) and microfloral overgrowth (especially of fermentation bacteria and yeasts due to the slightly more acidic gut contents) Husebye 2005). Improving diabetes complications, reducing prevalence and restoring normal physiological patterns should significantly optimise diabetes treatment and the quality of life for diabetic patients.…”
Section: Introductionmentioning
confidence: 99%